2011
DOI: 10.1158/1538-7445.am2011-5613
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 5613: Unclassified variants and missense polymorphisms in BRCA1 and BRCA2 genes in Algerian breast/ovarian cancer families

Abstract: Background: BRCA1 and BRCA2 germline mutations predispose heterozygous carriers to hereditary breast/ovarian cancer. Unclassified variants (UVs) and missense polymorphisms in BRCA genes pose a problem in genetic counseling, as their impact on risk of breast and ovarian cancer is still unclear. The objective of our present study is to characterize UVs and missense polymorphisms in Algerian breast/ ovarian cancer patients and relatives tested previously for BRCA1/2 genes germline mutations. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…Despite differences in the method of collecting data, the study populations and the distributions of clinical-pathologic variables considered in our study were fundamentally consistently between the 2 hospitals. The prevalence of germline mutations in BRCA1/2 varied by ethnicity (De Leon Matsuda et al, 2002;Cherbal et al, 2012;de Juan Jiménez et al, 2012;Stadler et al, 2012;Kim and Choi, 2013;Tariq et al, 2013;Hernández et al, 2014). We observed a higher prevalence of BRCA1/2 common polymorphisms in breast cancer cases and the control group and also found that a large number of Kazakh women carried ≥ 4 co-existing BRCA1/2 alterations, which is consistent with the previously reported findings for Kazakhstan (Akilzhanova et al, 2011) and Asian and European populations (Han et al, 2006;Song et al, 2006;Loizidou et al, 2007).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Despite differences in the method of collecting data, the study populations and the distributions of clinical-pathologic variables considered in our study were fundamentally consistently between the 2 hospitals. The prevalence of germline mutations in BRCA1/2 varied by ethnicity (De Leon Matsuda et al, 2002;Cherbal et al, 2012;de Juan Jiménez et al, 2012;Stadler et al, 2012;Kim and Choi, 2013;Tariq et al, 2013;Hernández et al, 2014). We observed a higher prevalence of BRCA1/2 common polymorphisms in breast cancer cases and the control group and also found that a large number of Kazakh women carried ≥ 4 co-existing BRCA1/2 alterations, which is consistent with the previously reported findings for Kazakhstan (Akilzhanova et al, 2011) and Asian and European populations (Han et al, 2006;Song et al, 2006;Loizidou et al, 2007).…”
Section: Discussionsupporting
confidence: 92%
“…Most studies on BRCA gene mutations have focused on western populations with a family history, ovarian cancer, or high cancer risks (Cherbal et al, 2012;Noh et al, 2014), and few studies have examined the role of the BRCA genes in Asian sporadic breast cancer populations (De Leon Matsuda et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Our observation is in line with a study that measured a total of 20% of BRCA1 or BRCA2 deleterious germline mutations (Henouda et al, 2016) on forty Algerian primary invasive unrelated BC cases who attended the Anti-Cancer Center of Setif. In addition, a second study conducted on an Algerian cohort of 70 families with a personal and family history of BC found the presence of a large BRCA1 and BRCA2 mutation spectrum in North African populations (Cherbal et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Co-occurrence of a VUS with a known disease-causing mutation, either from the same or the other BRCA gene, can provide evidence to classify the variant, especially if it is reported in multiple patients [Goldgar et al, 2008;Cherbal et al, 2012;Santos et al, 2014]. Cooccurrence data are used in two ways: in a Posterior Probability calculation [Goldgar et al, 2004], as it is one of its elements, and as a standalone criterion for classification.…”
Section: Co-occurrencesmentioning
confidence: 99%